Challenges and opportunities towards the road of universal health coverage (UHC) in Nepal: a systematic review - Chhabi Lal Ranabhat; Chun-Bae Kim; Ajanta Singh; Devaraj Acharya; Krishna Pathak; Basundhara Sharma; Shiva Raj Mishra (BMC, 2019)
Abstract Background Universal health coverage (UHC) assures all types of health service and protects all citizens financially in any conditions due to illness. Globally, the UN sustainable development goal (SDG) provides high priority for UHC as a health related goal. The National health system of Nepal has prioritized in similar way. The aim of this study is to explore the challenges and opportunities on the road to UHC in Nepal. Method We used varieties of search terminologies with popular search engines like PubMed, Google, Google Scholar, etc. to identify studies regarding Nepal's progress towards UHC. Reports of original studies, policies, guidelines and government manuals were taken from the web pages of Ministry of Health and its department/division. Searches were designed to identify the status of service coverage on UHC, financial protection on health particularly, health insurance coverage with its legal status. Other associated factors related to UHC were also explored and presented in Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) flow chart. Results We found 14 studies that were related to legal assurance, risk pulling and financing of health service, 11 studies associated to UHC service coverage status and, 7 articles linked to government stewardship, health system and governance on health care. Constitutional provision, global support, progress on the health insurance act, decentralization of health service to the grass root level, positive trends of increasing service coverage are seen as opportunities. However, existing volunteer types of health insurance, misleading role of trade unions and high proportion of population outside the country are main challenges. The political commitment under the changing political context, a sense of national priority and international support were identified as the facilitating factors towards UHC. Conclusion To achieve UHC, service and population coverage of health services has to be expanded along with financial protection for marginalized communities. Government stewardship, support of stakeholders and fair contribution and distribution of resources by appropriate health financing modality can speed up the path of UHC in Nepal.